2006
DOI: 10.1089/ten.2006.12.1881
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Analysis of Rat Hepatocyte Spheroids Generated on Poly(L-lactic acid) Polymer in a Pulsatile Flow Bioreactor

Abstract: Liver neo-tissue suitable for transplantation has not been established. Primary rat hepatocytes were cultured on three-dimensional biodegradable polymer matrices in a pulsatile flow bioreactor with the intention of inducing tissue formation and improving cell survival. Functional and structural analysis of the hepatocytes forming liver neo-tissue was performed. Biodegradable poly(L-lactic acid) (PLLA) polymer discs were seeded with 4 x 10(6) primary rat hepatocytes each, were exposed to a pulsatile medium flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…Such a 3D culture model has occurred to recapitulate many in vivo tissue structures and functions [3,9]. Very few hepatocyte spheroid models were established using: a poly-(L-lactic acid ) polymer [10], rock techniques [11], micro-rotation flows [12], alginate scaffolds [13], RGD and galactose-conjugated membranes [14], positive-charged substrates [4], micropatterning techniques [15], nanopillar sheets [16], galactosylated nanofiber scaffold [17], or polyurethane forms [18]. However, hepatocyte spheroids under the influence of fetal calf serum and nonparechyalmal cells have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Such a 3D culture model has occurred to recapitulate many in vivo tissue structures and functions [3,9]. Very few hepatocyte spheroid models were established using: a poly-(L-lactic acid ) polymer [10], rock techniques [11], micro-rotation flows [12], alginate scaffolds [13], RGD and galactose-conjugated membranes [14], positive-charged substrates [4], micropatterning techniques [15], nanopillar sheets [16], galactosylated nanofiber scaffold [17], or polyurethane forms [18]. However, hepatocyte spheroids under the influence of fetal calf serum and nonparechyalmal cells have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Further the study provides insight on scaffolds derived from ECM alone can induce further hepatocyte maturation when compared with bioplotted PLLA-collagen scaffolds [ 115 ] 35 Pulveriziation Natural ECM Human hepatic stem cell This study fabricated biomatrix scaffolds which can be used for biological and pharmaceutical studies. In future, this study promises to provide a platform for implantable, vascularized engineered tissues or organs [ 116 ] 36 Gelation Natural ECM primary human hepatocyte This study investigated the ability of 3D model with primary hepatocyte to support primary human hepatocyte specific functions in vitro [ 117 ] 37 3D Bioprinting Natural ECM HepG2, BMMSCs This study developed a liver decellularized extracellular matrix (dECM) bioink for 3D cell printing applications and evaluated various characteristics [ 118 ] 38 Spheroids PLLA Rat hepato cyte This study demonstrates a three-dimensional spheroids with applications for virology, toxicology, and drug development, in which metabolically active liver which proved to be more advantageous than monolayer hepatocyte cultures [ 119 ] 39 particulate leaching PLLA and gelatin coating Rat hepato cyte This study demonstrated PLLA and gelatin coating along with rat hepatocyte 3D model induced vascularization, which enabled a large attachment of cells [ 120 ] 40 Bioplotting PLLA and collagen iPSC This study used PLLA and collagen along with iPSC to establish a 3D model with clinical application using the tissue engineering in vivo . Further extracorporal liver assist device was established in this study [ 121 ...…”
Section: Liver Model Fabrication Techniquesmentioning
confidence: 99%
“…The results imply that cells sense the flow rate differently, and thus the perfusion conditions need to be adjusted. When the initial seeding and flow rate were optimized, the dynamic culture combined with 3D matrices could provide unique microenvironments for cells to grow and function favorably for liver repair and regeneration . For instance, a naturally self‐assembling peptide nanoscaffold was used as a matrix to allow culturing primary liver cells for as long as 35 d in a bioreactor in the presence of growth factors and cytokines.…”
Section: Culture Technologiesmentioning
confidence: 99%